A music- and game-based oral health education for visually impaired school children; multilevel analysis of a cluster randomized controlled trial - Nasrin Sharififard; Katayoun Sargeran; Mahdia Gholami; Farid Zayeri (BMC, 2020)
Abstract Background Visually impaired children encounter some challenges for their oral health. We aimed to compare the effectiveness of oral health education using Audio Tactile Performance (ATP) technique alone, ATP combined with oral health education for mothers, and ATP along with art package on the oral health status of visually impaired children. Materials and methods This cluster, randomized trial, included visually impaired children from preschool to 10th grade (32 classes, n = 200), in Tehran, Iran, in 2018-2019. A questionnaire was filled out through face to face interviews at baseline regarding age, gender, status of visual impairment, and place of residence. The Simplified Oral Hygiene Index (OHI-S) and Bleeding on Probing (BOP) were examined afterward. Classes were randomly assigned to three groups through simple randomization: 1. Art group (ATP, game-based, and music-based education (11 classes, n = 66); 2. Mothers group (children received ATP and their mothers received education by telephone (10 classes, n = 73); and 3. Control group (children received ATP (11 classes, n = 61). Children received reinforcement after 1 and 2 weeks. Follow-up oral examinations were performed after 1 and 2 months by a blind calibrated examiner. Descriptive statistics were performed using Chi-Square, and ANOVA tests by SPSS (version 22). In analytic statistics, two-level mixed-effects models for BOP and OHI-S were fitted using the Statistical Analysis Software (SAS) version 9.4. Both models fitted with the grouping variable and time (baseline, 1, and 2 months after interventions) as the fixed effects. Results The mean age (SD) of the children was 12.29 (3.45) years (range: 6-17). Male children (67%) more than female children (33%) participated in the study. Also, 35.5% were blind, and 12% resided at the dormitory. The art and mothers groups had no statistically significant difference compared with the control group, in terms of OHI-S (P = 0.92, and 0.39, respectively) and BOP (OR = 0.64, and 0.66, respectively). The time effect was statistically significant in both BOP and OHI-S models (P < 0.0001). Conclusions ATP technique is an effective method to improve the oral health status of visually impaired school children. Oral health promotion programs can be done using this method to tackle oral hygiene problems in visually impaired children. Trial registration ( https://www.irct.ir/trial/34676 : Nov 29th, 2018)